SUPPORTING CHARACTERS IN THE TALE OF KIEU - Lê Hồng Phong (Tạp chí Khoa học Đại học Đà Lạt)
Using the method of authentication to strictly follow the words of the work, this article reaffirms and explores the personalities, roles, and relationships of the supporting characters in “The Tale of Kieu”. This exploration is intended to discover Nguyen Du's intentions when he forgets, or temporarily forgets, certain supporting characters, including Kim Trong. The author also attempts to correct certain misassumptions of other researchers about some supporting characters in “The Tale of Kieu”.